A computational study of the effect of the metal organic framework environment on the release of chemically stored nitric oxide1. Issue 36 (28th September 2015) - Li, Tanping; Taylor-Edinbyrd, Kiara; Kumar, Revati
<x xml:space="preserve">Abstract</x> Computational investigations into the effect of a copper based metal organic framework on the sustained release of NO from S-nitrosothiols.